The factors of the given equation is (x-5) and (x+1).
Explanation:
Given,
y = -
![x^(2) +4x+5](https://img.qammunity.org/2021/formulas/mathematics/middle-school/jvn3rcbo02t71yklxut9ibbsja1nr86tfg.png)
To find the factors of the given equation.
We will apply middle term factor method.
To find the factor we have to take y = 0
So,
-
= 0
or,
![-x^(2) +(5-1)x+5 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/zuttfykuy4hvn67mg73wnyqb5zmgbqjvus.png)
or,
![-x^(2) +5x-x+5 = 0](https://img.qammunity.org/2021/formulas/mathematics/middle-school/p5j3h64j2csuhqxzd941dvvxsq9szdki6d.png)
or, -x(x-5)-1(x-5) = 0
or, (x-5)(-x-1) = 0
or, (x-5)(x+1) = 0
Hence,
The factors of the given equation is (x-5) and (x+1).